QUO VADIS GRANDES ECOLES: ECOLE NATIONALE D’ADMINISTRATION (ENA) - Kristian Widya Wicaksono (Yogyakarta State University, 2020)
In France, to reach a good career as the high-rank of government officials, people must join the Ecole National d’Administration (ENA). This situation put the ENA graduates (enarques) in the strategic position as the administrative elite but this special privilege gives the word egalité within higher education a hollow sound. This paper wants to know the impact of Ernarques on the merit system recruitments of high-rank civil servants. The method used in this paper writing is a systematic literature review. The results of this study show that it is not compulsory to dissolve ENA but we should treat ENA as an ordinary school for Public Administrator. Then, it is important to create another university that has the same concentration and access as ENA to procreate a fair competition. Finally, we must invite diverse graduates to join the high-rank position to encourage innovation and competitive nuance in the public organization.